Evaluation and comparison of the ergonomics, performance and economics of battery-powered and engine-powered palm oil harvesting tools:cantas elektro - Ahmad Syazwan Ramli,; Mohd Azwan Mohd Bakri,; Aminulrashid Ibrahim,; Mohd Faudzi,; Ahmad Athif Ariff Azly Muhamed,; Habiel Zakariah, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Malaysian Palm Oil Board (MPOB) has introduced an engine-powered palm oil harvesting tool called CANTAS that can double the conventional harvesting output. However, there are several issues that are affecting the endurance and comfort of the harvesters. This paper discusses the comparison in the context of ergonomics, performance, and ecconomics of a battery-powered CANTAS called CANTAS Elektro, which could overcome the issues of the engine-powered CANTAS. The prototype was tested in the laboratory and the field to investigate its ergonomic factors. Test results revealed that CANTAS Elektro was more ergonomic than CANTAS as the deflection, configuration, temperature, noise, and vibration levels of the former were 38%, 42%, 59.8%, 12.7%, and 45.8–65.2% less than those of the latter, respectively. The harvesting productivity increased by 26.5% from 5.63 to 7.04 t/day, with an estimated saving of operational cost of RM1013/machine/yr. The take-home pay of workers was increased by 29% from RM81 to RM107/man-day, apart from other fringe benefits. It was proven that the battery-powered machine was more cost-effective than the engine-powered machine, in addition to other advantages such as being carbon emission-free, clean, easy to maintain, less complicated and easy to handle.